Mediale Hochschul-Perspektiven 2020 in Baden-Württemberg : empirische Untersuchung im Rahmen der Allianz ""Forward IT"" - Gidion, Gerd [Hrsg.]Weyrich, Michael [Hrsg.]Grosch, Michael [Mitarb.]Hartmann, Jörg [Mitarb.]Holstein, Sarah [Mitarb.]Marks, Philipp [Mitarb.]Sexauer, Andreas [Mitarb.]Zafirov, Aleksandar [Mitarb.] (KIT Scientific Publishing, 2017)
The study explores digitization in higher education from the organizational perspective of a university as a "model", illustrated through specific case studies of the Karlsruhe Institute of Technology and the University of Stuttgart. It is assumed that the key factors affecting digitization in higher education are the widespread adoption and usage of digital technology in science, the digital interconnectedness of higher education systems and the media usage habits of instructors and students.